Scrppless Tranding - Emiel Salim Siregar; Galang Ramadhan Dalimunte; Tengku Kumala Sari; Dwika Darmansyah; Muhammad Idrus (Jurnal Warta Dharmawangsa, 2026)
The development of information technology has driven a major transformation in modern trading systems, one of which is through the emergence of the concept of Scrapless Trading. This study aims to examine the background, principles, characteristics, processes, benefits, implementation, and impacts of Scrapless Trading on the business world and the economy. The discussion results show that Scrapless Trading emerged as a response to the need for efficiency, speed, and accuracy in increasingly complex transactions in the digital era. This system is supported by technologies such as cloud computing, artificial intelligence, and real-time data integration that enable trading processes to run automatically and in an organized manner. In terms of principles and characteristics, Scrapless Trading emphasizes automation, data integration, and transparency, with the features primarily the minimal human intervention and the high speed of transaction processes. The mechanism of this system includes stages of data input, automatic verification, transaction execution, up to digital-based monitoring and reporting. Its implementation in the business world has proven to be able to increase operational efficiency, productivity, and quality of service to consumers. In addition, this system also provides various benefits, such as reducing operational costs, increasing data accuracy, transaction transparency, and flexibility in transactions. In the economic context, Scrppless Trading has a positive impact in the form of increased market efficiency, digital economy growth, and expansion of business opportunities, especially for MSME actors. However, there are also challenges that need to be considered, such as technological infrastructure gaps, low digital literacy, as well as data security risks and workforce reduction due to automation